Differences in Glycerolipid Response of Chlamydomonas reinhardtii Starchless Mutant to High Light and Nitrogen Deprivation Stress Under Three Carbon Supply Regimes - Yang, Miao; Xie, Xi; Kong, Fan-Tao; Xie, Kun-Peng; Yu, Si-Hui; Ma, Jing-Yi; Xue, Song; Gong, Zheng (Frontiers in Plant Science, 2022)
Carbon source serves as a crucial factor for microalgal lipid biosynthesis. The supplied exogenous inorganic or organic carbon affects lipid accumulation in microalgae under stress conditions. However, the impacts of different carbon availability on glycerolipid metabolism, triacylglycerol (TAG) metabolism in particular, still remain elusive in microalgae. Chlamydomonas starchless mutant BAFJ5 has emerged as a model system to study TAG metabolism, due to its property of hyper-accumulating TAG. In this study, the glycerolipidomic response of the starchless BAFJ5 to high light and nitrogen-deprived (HL-N) stress was deciphered in detail to distinguish glycerolipid metabolism under three carbon supply regimes. The results revealed that the autotrophically and mixotrophically grown BAFJ5 cells aerated with air containing 2% CO2 presented similar changes in growth, photosynthetic activity, biochemical components, and glycerolipid metabolism under HL-N conditions. But the mixotrophically grown BAFJ5 aerated with air containing 0.04% CO2 exhibited more superior accumulation in TAG, which was esterified with a significantly higher proportion of C18:1n9 and prominently the lower proportions of polyunsaturated fatty acids. In addition, these cells increased the relative levels of C18:2n6 in the membrane lipids, i.e., monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG), in priority, and decreased that of C18:3n3 and C18:4n3 in the betaine lipid, N,N,N-trimethylhomoserine diacylglycerol (DGTS), subsequently, to adapt to the HL-N stress conditions, compared to the cells under the other two conditions. Thus, it was suggested that C. reinhardtii starchless mutant appeared to present distinct metabolism for TAG biosynthesis involving membrane lipid remodeling under distinct carbon supply regimes. This study provides insights into how the different carbon supply regimes affect lipid metabolism in Chlamydomonas starchless cells, which will benefit the optimized production of storage lipids in microalgae.